Terra dos animais da floresta: análise das relações entre humanos e outros seres no território, e seus arredores, ocupado pela Reserva Biológica de Sooretama - Santos, Claudia Farias Gomes dos (2023)
This work deals with the analysis of the established relations between sooretamenses family farmers and other beings in a territory, and their adjacencies, currently occupied by the Biological Reserve of Sooretama, a natural protected area, located in the north region of Espírito Santo state (ES). The organized discussion is registered in the field of the studies of social sciences referred to human and non-human relations. The work consists on the observation and experiencing of the ways of being and living from rural communities next to this protected area. We can affirm that our interest is in the peculiarities and complexities presented in human interactions with the environment. This research deals with socioenvironmental issues which considers the world conjoint constitution, especially in its territorial dimensions. Although it has not been our initial goal, the analyses promoted here, allowed to consider, as well, how these humans and the non-humans with whom this territory is shared constitute plural morethan-human landscapes that extrapolate the topographic boundaries of this conservation area.